Lithium ion battery negative electrode material with high stability and long cycle life and preparation method thereof

By integrating the multi-layer Ti3C2Tx skeleton with the dual heterostructure of Ti3C2Tx@TiO2 and Ti3C2Tx@La2O3 in the negative electrode material of lithium-ion battery, the shortcomings in the existing materials in electrochemical stability and service life are solved, and the preparation of negative electrode materials with high stability and long cycle life is achieved.

CN119581531AActive Publication Date: 2025-03-07HUNAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411778441.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have problems such as poor electrochemical stability and short service life during charging and discharging, especially when recombining with MXene, such as poor conductivity, low rate performance, poor electrode stability and complex preparation process.

Method used

The multi-layer Ti3C2Tx skeleton is used to combine with the dual heterostructures of Ti3C2Tx@TiO2 and Ti3C2Tx@La2O3 to form a high stability and long cycle life of lithium-ion battery negative electrode material. This material is prepared by hydrothermal oxidation method, and TiO2 and La2O3 are used as structural stabilizers and active substances to improve the conductivity and stability of the material.

Benefits of technology

The high conductivity, high capacity and high stability of the negative electrode material of lithium-ion battery is achieved, the rate performance and overall stability of lithium-ion are improved, the battery maintains good performance under different current densities, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581531A_ABST
    Figure CN119581531A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery negative electrode material with high stability and long cycle life. The lithium ion battery negative electrode material comprises a multi-layer Ti < 3 > C < 2 > T < x > (at) TiO2 heterostructure combined with the multi-layer Ti < 3 > C < 2 > T < x > (at) TiO2 heterostructure and a Ti < 3 > C < 2 > T < x > (at) La2O3 heterostructure combined with the multi-layer Ti < 3 > C < 2 > T < x > (at) La2O3 heterostructure. The electrode material has the advantages of high conductivity, high capacity, high stability and the like by integrating the double heterostructures of the Ti3C2Tx-coated TiO2 and the Ti3C2Tx-coated La2O3 in the same electrode, and meanwhile, the double heterostructures effectively improve the rate capability and the overall stability of lithium ions, so that the battery can keep relatively good performance under different current densities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery negative electrode material with high stability and long cycle life and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and no memory effect. As the global demand for renewable energy and electric vehicles continues to increase, the market prospects for lithium-ion batteries are becoming more and more broad. In addition, with the popularization of portable electronic devices and the rapid development of the electric vehicle industry, the market demand for efficient, portable, and safe energy storage devices is also rising sharply. Advances in energy storage technology can not only support the wider application of renewable energy, but also meet the specific needs of these emerging fields for energy storage. Therefore, the development of energy storage technology plays a vital role in promoting energy transformation and promoting environmental protection, and it also requires continuous innovation to meet the growing market demand.

[0003] However, although traditional negative electrode materials, such as graphite, perform well in some aspects, they still have certain shortcomings in terms of long battery life, fast charging and discharging, and high temperature stability. In recent years, researchers have been exploring high-performance negative electrode materials to improve the overall performance of batteries. The development of long-life lithium-ion battery negative electrode materials has become an important research direction. In this context, silicon-based materials, alloy materials, carbon-based composite materials, etc. have gradually attracted attention. Although these materials have high theoretical capacity, their volume expansion is significant during the charging and discharging process, resulting in poor cycle stability. Therefore, the application of modification and composite technology is imperative to effectively inhibit the expansion phenomenon and improve the cycle efficiency. By optimizing the material structure, improving the interface interaction and regulating the particle size, scientists are committed to improving the cycle life and rate performance of negative electrode materials, providing more reliable solutions for the future application of lithium-ion batteries. This will not only promote the development of green energy technology, but also have important significance for promoting the process of sustainable society.

[0004] Since the service life and stability of materials are limited by the physical and chemical properties of the materials themselves, such as poor cycle stability, which leads to a low battery service life, its commercial application is seriously hindered. Among them, MXene materials, as a new type of transition metal carbonitride, have high intrinsic electronic conductivity and can achieve high-rate charge and discharge, but their capacity and working life are insufficient. Therefore, the current research direction of researchers on MXene is mainly focused on composite high capacity and design of new morphology. However, MXene-based lithium-ion battery negative electrode materials still face the following problems:

[0005] 1) The second phase material composited with MXene has poor conductivity and low rate performance;

[0006] 2) MXene-based lithium-ion battery negative electrode materials have poor electrode stability, fast capacity decay, and short service life;

[0007] 3) The preparation process of MXene-based lithium-ion battery negative electrode materials is complex and the cost is too high, making it difficult to achieve commercial production. Summary of the invention

[0008] The purpose of the present invention is to provide a highly stable and long cycle life lithium ion battery negative electrode material and a preparation method, which can effectively shorten the migration and diffusion energy barriers of lithium ions in the electrode and improve the structural stability during lithium ion transmission, thereby solving the problems of poor electrochemical stability and short service life of lithium ion battery negative electrode materials during charging and discharging.

[0009] In order to achieve the above purpose, the following technical solutions are adopted:

[0010] A highly stable lithium-ion battery negative electrode material with a long cycle life, comprising multilayer Ti3C2T x skeleton, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @TiO2 heterostructure, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @La2O3 heterostructure.

[0011] Furthermore, in the negative electrode material, the active material content accounts for 95%, wherein the active material is multilayer Ti3C2T x framework and TiO2 nanoparticles, with La2O3 acting as a structural stabilizer.

[0012] Furthermore, the multilayer Ti3C2T x The diameter of the skeleton is between 3 and 5 μm, and the diameters of TiO2 and La2O3 are between 50 and 100 nm.

[0013] A method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life is also provided, which is used to prepare the above-mentioned negative electrode material, comprising the following steps:

[0014] S1: The MAX phase Ti3AlC2 material is sequentially etched, centrifuged, and freeze-dried to obtain a multilayer Ti3C2T x Powder materials;

[0015] S2: a certain mass of multilayer Ti3C2T x The powder material is dissolved in deionized water and ultrasonically treated in an ice bath for a period of time to form solution A;

[0016] S3: adding an appropriate amount of La2O3 precursor material LaN3O9·6H2O into solution A and mixing them evenly to form a mixed solution B;

[0017] S4: placing the mixed solution B in a polytetrafluoroethylene reactor, and continuously inputting inert gas Ar2 into the polytetrafluoroethylene reactor for a period of time, then sealing the polytetrafluoroethylene reactor and performing a hydrothermal reaction;

[0018] S5: Filter and clean the product obtained by the hydrothermal reaction in S4 to obtain Ti3C2T x @La2O3 heterostructure material, and place it in a vacuum drying oven and dry it for a period of time to obtain Ti3C2T x @La2O3 powder material;

[0019] S6: Add a certain amount of Ti3C2T x @La2O3 powder material is added to deionized water and ultrasonically treated to obtain a suspension, which is then placed in a polytetrafluoroethylene reactor, and inert gas Ar2 is continuously introduced into the polytetrafluoroethylene reactor for a period of time to form a low-oxygen atmosphere, and then a hydrothermal reaction is carried out in the low-oxygen atmosphere;

[0020] S7: The product obtained by the hydrothermal reaction of S6 is filtered and cleaned to obtain Ti3C2T x @TiO2 / Ti3C2T x @La2O3 double heterostructure material and dry it.

[0021] Furthermore, in S1, the MAX phase Ti3AlC2 material is etched by using hydrofluoric acid with a concentration of 20%, and the etched product is added to a mixture of deionized water and anhydrous ethanol for centrifugal treatment.

[0022] Furthermore, in S2, the multilayer Ti3C2T x The mass of the powder material is 0.5 g, the deionized water is 20 ml, and the time of ice bath ultrasonic treatment is 20 min; in S3, the corresponding amount of LaN3O9·6H2O is weighed and added to solution A according to the molar ratio of Ti:La element of 4%, 8%, or 10%.

[0023] Furthermore, in S4, the mixed liquid B is placed in a 50 ml polytetrafluoroethylene reactor, and the time for inputting inert gas Ar2 into the polytetrafluoroethylene reactor is 15 minutes, the temperature of the hydrothermal reaction is 140°C, and the time of the hydrothermal reaction is 24 hours; in S5, the temperature of the vacuum drying oven is 70°C, and the drying time is 12 hours.

[0024] Furthermore, in the S6, Ti3C2Tx @The mass of La2O3 powder material is 0.5g, the deionized water is 30ml, the polytetrafluoroethylene reactor is 50ml, the time of inputting inert gas Ar2 into the polytetrafluoroethylene reactor is 10s, the time of hydrothermal reaction is 12h, and the temperature of hydrothermal reaction is 80℃; in S7, Ti3C2T x @TiO2 / Ti3C2T x @La2O3 double heterostructure material was placed in a vacuum drying oven at 70°C and dried for 12 h.

[0025] By adopting the above scheme, the beneficial effects of the present invention are:

[0026] The present invention integrates Ti3C2T in the same electrode x @TiO2 and Ti3C2T x @The double heterostructure of La2O3 gives the electrode material the advantages of high conductivity, high capacity and high stability. At the same time, this double heterostructure effectively improves the rate performance and overall stability of lithium ions, allowing the battery to maintain good performance at different current densities. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A brief flow chart of the preparation of negative electrode materials for lithium-ion batteries of the present invention;

[0028] Figure 2 This is a SEM image of a lithium-ion negative electrode material of the present invention;

[0029] Figure 3 This is a test diagram of the rate performance of a lithium-ion negative electrode at different current densities in one embodiment of the present invention;

[0030] Figure 4 This is a test diagram of the electrochemical impedance spectroscopy of a lithium ion negative electrode in one embodiment of the present invention;

[0031] Figure 5 This is a GCD curve diagram of a lithium-ion negative electrode at a current density of 100 mA / g and different numbers of cycles in one embodiment of the present invention;

[0032] Figure 6 This is a test diagram of the cycle performance of a lithium-ion negative electrode at a current density of 100 mA / g in one embodiment of the present invention;

[0033] Figure 7 This is a long cycle performance test diagram of a lithium-ion negative electrode at a current density of 1 A / g in one embodiment of the present invention. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0035] Reference Figures 1 to 7 As shown, the present invention provides a lithium ion battery negative electrode material with high stability and long cycle life. In one embodiment, it includes a multilayer Ti3C2T x skeleton, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @TiO2 heterostructure, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @La2O3 heterostructure.

[0036] In this embodiment, multilayer Ti3C2T x It is a carrier and source material, which belongs to a two-dimensional layered transition metal carbonitride, in addition to Ti4C3T x 、Ti2CT x 、V2CT x 、Nb2CT x etc., where T x Represents the functional groups of MXene, which are composed of -OH, -O, -F, -Cl, etc.; TiO2 is a multilayer Ti3C2T x derivatives, which are similar to Ti3C2T x The skeleton is combined to increase the electrochemical activity of the material; La2O3 acts as a structural stabilizer and combines with Ti3C2T x The skeleton is combined to improve the structural stability of the material; at the same time, the active material content accounts for 95%, wherein the active material is multilayer Ti3C2T x Framework and TiO2 nanoparticles.

[0037] In one embodiment, the multilayer Ti3C2T x The diameter of the skeleton is between 3 and 5 μm, and the diameters of TiO2 and La2O3 are between 50 and 100 nm. x The skeleton is prepared by hydrofluoric acid etching, and forms a three-dimensional accordion structure at room temperature, wherein the precursor material is Ti3AlC2 ceramic material.

[0038] In summary, the negative electrode material of the present invention exhibits an accordion structure in physical morphology and a chemical microscopic appearance of Ti3C2T x @TiO2 / Ti3C2T x @La2O3 double heterostructure, that is, double heterostructure integrated on the same electrode, can effectively reduce the lithium ion migration and diffusion energy barriers, thereby optimizing the lithium ion transmission path (in actual application, the diameter of the negative electrode material can be cut to 1.2cm, and the mass is in the range of 1.5 to 2mg).

[0039] A method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life is also provided, which is used to prepare the above-mentioned negative electrode material. The preparation method is a native hydrothermal oxidation method, which is to form a multilayer Ti3C2T x The material and the La2O3 precursor are mixed hydrothermally and then hydrothermally oxidized in a low oxidation atmosphere, specifically comprising the following steps:

[0040] S1: The MAX phase Ti3AlC2 material is sequentially etched, centrifuged, and freeze-dried to obtain a multilayer Ti3C2T x Powder material.

[0041] In this step, the MAX phase Ti3AlC2 material is first etched with hydrofluoric acid at a concentration of 20% to remove the Al element in Ti3AlC2, thereby obtaining a Ti3C2Tx (MXene) material composed of Ti, C and N; then, the etched product is added to a mixture of deionized water and anhydrous ethanol for centrifugal treatment to remove excess acid and by-products. The centrifugation is to separate the solid and liquid in the solution to remove insoluble impurities or collect precipitates. Finally, the obtained solid material is dried by freeze-drying technology to avoid possible chemical changes in the material at high temperatures while maintaining the porous structure and shape of the material.

[0042] S2: a certain mass of multilayer Ti3C2T x The powdered material was dissolved in deionized water and subjected to ultrasonic treatment in an ice bath for a period of time to form solution A.

[0043] In this step, 0.5 g of multilayer Ti3C2T x The powder material was dissolved in 20 ml of deionized water and ultrasonically treated in an ice bath for 20 min to fully disperse the solid particles in the solution to form a uniform solution A.

[0044] S3: Add an appropriate amount of La2O3 precursor material LaN3O9·6H2O into solution A and mix well to form a mixed solution B.

[0045] In this step, firstly, according to the molar ratio of Ti:La element substance of 4%, 8%, or 10%, a corresponding amount of LaN3O9·6H2O is weighed, and added into solution A, and mixed evenly to form a mixed solution B.

[0046] S4: placing the mixed liquid B in a polytetrafluoroethylene reactor, and continuously inputting inert gas Ar2 into the polytetrafluoroethylene reactor for a period of time, then sealing the polytetrafluoroethylene reactor and performing a hydrothermal reaction.

[0047] In this step, the mixed solution B is first placed in a 50 ml polytetrafluoroethylene reactor, and then the inert gas Ar2 is continuously introduced into the polytetrafluoroethylene reactor for 15 minutes to remove the air in the reactor and prevent oxygen and moisture from interfering with the reaction, thereby avoiding possible side reactions. Subsequently, the polytetrafluoroethylene reactor is sealed and a hydrothermal reaction is performed. The temperature of the hydrothermal reaction is 140°C and the time of the hydrothermal reaction is 24 hours. Under this condition, LaN3O9·6H2O will be converted into La2O3 and react with Ti3C2T x Forming a composite material.

[0048] S5: Filter and clean the product obtained by the hydrothermal reaction in S4 to obtain Ti3C2T x @La2O3 heterostructure material, and place it in a vacuum drying oven and dry it for a period of time to obtain Ti3C2T x @La2O3 powder material.

[0049] In this step, the product obtained by the hydrothermal reaction is first filtered and cleaned to remove unreacted raw materials, by-products or other impurities to obtain Ti3C2T x @La2O3 heterostructure material, and then placed it in a vacuum drying oven at 70°C for 12 hours to remove moisture and obtain Ti3C2T x @La2O3 powder material.

[0050] S6: Add a certain amount of Ti3C2T x @La2O3 powder material is added to deionized water and ultrasonically treated to obtain a suspension, which is then placed in a polytetrafluoroethylene reactor, and inert gas Ar2 is continuously introduced into the polytetrafluoroethylene reactor for a period of time to form a low-oxygen atmosphere, and then a hydrothermal reaction is carried out in the low-oxygen atmosphere.

[0051] In this step, 0.5 g of Ti3C2T x The powder material @La2O3 was added to 30 ml of deionized water for ultrasonic treatment to evenly disperse the powder in the water to form a suspension. Subsequently, the obtained suspension was placed in a 50 ml polytetrafluoroethylene reactor and introduced with inert gas Ar2 for 10 seconds to exhaust the air in the reactor and form a low oxygen environment. Finally, a hydrothermal reaction was carried out in the low oxygen atmosphere to make Ti3C2T x TiO2 was in situ grown on the surface of La2O3 powder, wherein the hydrothermal reaction time was 12 h and the hydrothermal reaction temperature was 80°C.

[0052] S7: The product obtained by the hydrothermal reaction of S6 is filtered and cleaned to obtain Ti3C2T x @TiO2 / Ti3C2Tx @La2O3 double heterostructure material and dry it.

[0053] In this step, the product obtained by the hydrothermal reaction in step S6 is first filtered and cleaned to remove unreacted raw materials, by-products or other impurities to obtain a double heterostructure material containing Ti3C2Tx@TiO2 and Ti3C2Tx@La2O3, and the obtained material is placed in a vacuum drying oven at 70°C and dried for 12 hours to remove moisture, finally obtaining a dry negative electrode material with high stability and long cycle life.

[0054] The Ti3C2T prepared by the above method x @TiO2 / Ti3C2T x @La2O3 double heterostructure materials can be named ML4, ML8, ML10 according to different molar ratios (4%, 8%, 10%), such as Figure 2 As shown in the figure, TiO2 and a small amount of La2O3 nanoparticles are evenly distributed in the multilayer Ti3C2T x layer, where multilayer Ti3C2T x The total mass ratio of Ti3C2T4O3 is about 95%, and the mass ratio of La2O3 is 5%. At the same time, the material prepared by the above method can be directly used in lithium-ion batteries, in which the electrolyte is lithium hexafluorophosphate, ethylene carbonate and dimethyl carbonate. In addition, the battery negative electrode material prepared by the above method has a unique Ti3C2T4O3 structure. x @TiO2 and Ti3C2T x @La2O3 double heterostructure, in which Ti3C2T x It plays a role in improving the electronic conductivity and active substances of the composite material. TiO2 prepared by low-temperature in-situ oxidation strategy is the active substance, and La2O3 plays a role in stabilizing the structure. At the same time, this double heterogeneous structure can effectively reduce the migration and diffusion energy barriers of lithium ions, optimize the ion transmission path, stabilize the electrode microstructure, and thus improve the long-cycle performance of the electrode and increase the battery life.

[0055] In one embodiment, a negative electrode sheet is provided, comprising a current collector, and a conductive agent, a binder and the negative electrode material attached to at least one side of the current collector. In this embodiment, the electrode sheet is prepared by coating, wherein the ratio of active material: conductive agent: binder is 8:1:1.

[0056] In one embodiment, a battery is provided, comprising a positive electrode sheet, a separator, an electrolyte, a battery casing, and the above-mentioned negative electrode sheet. The electrode sheet can be assembled in the lithium-ion battery casing through processes such as pressing and weighing, wherein the electrolyte is lithium hexafluorophosphate, ethylene carbonate, and dimethyl carbonate.

[0057] The Ti3C2T prepared above x @TiO2 / Ti3C2T x @La2O3 double heterostructure material was tested for lithium-ion battery negative electrode, where the current density of rate performance test was 50mA / g, 100mA / g, 200mA / g, 500mA / g, 1A / g, 2A / g, 5A / g, and then returned to 50mA / g; the current density of long cycle performance test was 100mA / g and 1A / g. The test results show that when the molar ratio of Ti:La is 100:4, the material has the best performance.

[0058] At the same time, the Ti3C2T prepared above x @TiO2 / Ti3C2T x When La2O3 double heterostructure materials are directly used as lithium-ion negative electrodes, in testing the rate performance of lithium-ion batteries, such as Figure 3 As shown, when the test current density is 50mA / g, 100mA / g, 200mA / g, 500mA / g, 1A / g, 2A / g and 5A / g, after 5 cycles respectively, the capacity is 449, 191, 163, 121, 102, 79 and 59mAh / g respectively.

[0059] The test results show that the Ti3C2T prepared by the above embodiment x @TiO2 / Ti3C2T x When La2O3 double heterostructure materials are directly used as lithium-ion negative electrodes, they exhibit lower impedance ( Figure 4 ), explaining its high rate performance.

[0060] At the same time, if Figure 5 As shown, the Ti3C2T prepared above x @TiO2 / Ti3C2T x @La2O3 double heterostructure electrode at low current 100mA g -1 Under the condition of high temperature, after working for 800 cycles, the DC charge and discharge curve (GCD) remains unchanged, showing good chemical stability.

[0061] like Figure 6 As shown in the figure, when testing the long cycle performance of lithium-ion batteries, the current density is 100 mA / g, and the Ti3C2T x @TiO2 / Ti3C2T x @After 800 cycles, the capacity of the lithium-ion battery assembled with La2O3 double heterostructure materials remained at 319mAh / g.

[0062] The test results show that if Figure 7 As shown, when the current density is 1A / g, Ti3C2T x@TiO2 / Ti3C2T x @After 10,000 cycles, the capacity retention rate of the lithium-ion battery assembled with La2O3 double heterostructure materials is 101%.

[0063] The low-temperature hydrothermal oxidation strategy in this invention can be extended to MXene materials with high theoretical specific capacity derivatives but low conductivity and poor stability, such as V2CT x 、Mo2CT x etc., which is beneficial to improve the chemical stability of the electrode and increase the service life of the electrode. At the same time, the lithium ion battery negative electrode provided by the present invention has the following advantages:

[0064] First of all, the synthesis method is relatively simple. Ti3C2T can be obtained through hydrothermal and low oxidation atmosphere hydrothermal processes. x @TiO2 / Ti3C2T x @La2O3 double heterostructure. At the same time, the double heterostructure electrode material has the advantages of high stability and long cycle life. Moreover, the simple preparation process and operation flow are suitable for large-scale industrial production.

[0065] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly stable and long cycle life lithium ion battery negative electrode material, characterized in that: Including multi-layer Ti3C2T x skeleton, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @TiO2 heterostructure, and the multilayer Ti3C2T x Framework-bonded Ti3C2T x @La2O3 heterostructure.

2. The highly stable and long cycle life lithium ion battery negative electrode material according to claim 1, characterized in that: The content of active material in the negative electrode material accounts for 95%, wherein the active material is multilayer Ti3C2T x framework and TiO2 nanoparticles, with La2O3 acting as a structural stabilizer.

3. The highly stable and long cycle life lithium ion battery negative electrode material according to claim 1, characterized in that: The multilayer Ti3C2T x The diameter of the skeleton is between 3 and 5 μm, and the diameters of TiO2 and La2O3 are between 50 and 100 nm.

4. A method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life, used for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1: The MAX phase Ti3AlC2 material is sequentially etched, centrifuged, and freeze-dried to obtain a multilayer Ti3C2T x Powder materials; S2: a certain mass of multilayer Ti3C2T x The powder material is dissolved in deionized water and ultrasonically treated in an ice bath for a period of time to form solution A; S3: adding an appropriate amount of La2O3 precursor material LaN3O9·6H2O into solution A and mixing them evenly to form a mixed solution B; S4: placing the mixed solution B in a polytetrafluoroethylene reactor, and continuously inputting inert gas Ar2 into the polytetrafluoroethylene reactor for a period of time, then sealing the polytetrafluoroethylene reactor and performing a hydrothermal reaction; S5: Filter and clean the product obtained by the hydrothermal reaction in S4 to obtain Ti3C2T x @La2O3 heterostructure material, and place it in a vacuum drying oven and dry it for a period of time to obtain Ti3C2T x @La2O3 powder material; S6: Add a certain amount of Ti3C2T x @La2O3 powder material is added to deionized water and ultrasonically treated to obtain a suspension, which is then placed in a polytetrafluoroethylene reactor, and inert gas Ar2 is continuously introduced into the polytetrafluoroethylene reactor for a period of time to form a low-oxygen atmosphere, and then a hydrothermal reaction is carried out in the low-oxygen atmosphere; S7: The product obtained by the hydrothermal reaction of S6 is filtered and cleaned to obtain Ti3C2T x @TiO2 / Ti3C2T x @La2O3 double heterostructure material and dry it.

5. The method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life according to claim 4, characterized in that: In S1, the MAX phase Ti3AlC2 material is etched by using hydrofluoric acid with a concentration of 20%, and the etched product is added to a mixture of deionized water and anhydrous ethanol for centrifugal treatment.

6. The method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life according to claim 4, characterized in that: In S2, multilayer Ti3C2T x The mass of the powder material is 0.5 g, the deionized water is 20 ml, and the time of ice bath ultrasonic treatment is 20 min; in S3, the corresponding amount of LaN3O9·6H2O is weighed and added to solution A according to the molar ratio of Ti:La element of 4%, 8%, or 10%.

7. The method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life according to claim 4, characterized in that: In the S4, the mixed liquid B is placed in a 50ml polytetrafluoroethylene reactor, and the time for inputting inert gas Ar2 into the polytetrafluoroethylene reactor is 15 minutes, the temperature of the hydrothermal reaction is 140°C, and the time of the hydrothermal reaction is 24 hours; in the S5, the temperature of the vacuum drying oven is 70°C, and the drying time is 12 hours.

8. The method for preparing a lithium-ion battery negative electrode material with high stability and long cycle life according to claim 4, characterized in that: The S6, Ti3C2T x @The mass of La2O3 powder material is 0.5g, the deionized water is 30ml, the polytetrafluoroethylene reactor is 50ml, the time of inputting inert gas Ar2 into the polytetrafluoroethylene reactor is 10s, the time of hydrothermal reaction is 12h, and the temperature of hydrothermal reaction is 80℃; in S7, Ti3C2T x @TiO2 / Ti3C2T x @La2O3 double heterostructure material was placed in a vacuum drying oven at 70°C and dried for 12 h.

Citation Information

Patent Citations

  • A preparation method of two-dimensional heterostructure material for lithium sulfur battery

    CN108987653A

  • N-TiO2 / Ti3C2Tx heterogeneous MXene structural material as well as preparation and application thereof

    CN114039060A